Influence of Human Resource Practices and Employee Turnover on Organization Performance in Selected Commercial Banks in Pakistan - Muzammil, Rozina (2024)
The objective of this research study was to analyze the impact Job Satisfaction, career planning, organizational culture, training and development, employee engagement practices and employee turnover have on organizational performance in the banking sector of Pakistan. The research evaluated the mediating impact of employee turnover in the relationship between Human resources practices and organizational performance. Employee retention is low in the banking sector as employees leave due to low motivation and a high burden of work. The personal and demographic factors are the core reasons found by researchers. In the banking sector, it has been found that the lack of organizational commitment, Job Factors, and Job Satisfaction are the determinants of employee retention. This research has been conducted within the Pragmatism research paradigm which is the combination of both Positivism and Interpretivism. The data has been collected from Officers, Senior Officers, Managers, Vice Presidents, Senior Vice Presidents, and Executive Vice Presidents working in Commercial Banks of Pakistan through questionnaires and interviews. The sample of 385 responses was collected through a self-administered questionnaire from middle and top managers/executives of banks, and five in-depth interviews of Senior Bankers were also conducted to analyze the factors affecting employee turnovers and organizational performance. The research results were analyzed through SPSS Software for quantitative data analysis and NVivo was used to analyze the qualitative data collected from respondents. Structural Equation Modeling (SEM) is was applied to analyze the direct and indirect impacts of variables on employee turnover in the banking industry. The research results reveal that the data reliability of the scale wassignificant and values of Cronbach’s Alpha for all variables were greater than 0.7 which shows the scale used to collect the data was reliable. The structural model analysis was applied to evaluate the significant impact of variables, with Job Satisfaction, Career Planning and development, Organizational culture, training and development, and employee engagement practices as independent variables, Employee Turnover as mediator, and Organization performance as dependent variable. The results showed that Job Satisfaction, Organizational culture, training, and development have a significant impact on employee turnover, and employee turnover has a significant impact on organizational performance in the banking industry based on ‘t’ statistics and probability values of direct effects in SEM. The research results of indirect effects showed that the analysis variable employee turnover has a significant mediating impact on the relationship between Job Satisfaction, Career Planning and Development, Organizational culture and organizational performance, and the other two variables i.e. organizational training and employee engagement did not show the mediating impact. Eleven hypotheses were developed and tested in this research study. This research was focused on the banking sector in Pakistan. The study’s emphasis was on commercial banks and employees working in commercial banks. Due to the limitations of cost and time, the researcher was unable to include all conventional banks in Pakistan. The research is useful for the banking sector in Pakistan to analyze employee retention practices, considering that employee turnover is a critical factor for organizations. Banks need to focus on Job Satisfaction, Organizational culture, and Training and Development to keep employees motivated within their organizations. The findings and results of the research can only be generalized to organizations operating in the banking sector in Pakistan. The study will not contribute to the whole Financial Sector of Pakistan; the focus was only on Pakistan's Commercial Banks. This research will assist in understanding the mere impact of employees and organization performance to maintain the manpower in Banks. This research will identify the reasons/issues involved in employee turnover in Commercial banks in Pakistan and get control over factors identified for employee turnover. The research related to HR practices in Pakistani commercial banks has focused on several constructs individually or in diverse combinations: which are: job satisfaction, career planning, organizational culture, training, and employee engagement. Moreover, research has extensively contributed to the assessment of the impact of the above-mentioned constructs on employee turnover, and similarly, research has significantly contributed to the analysis of the mediating role played by employee turnover in the relationship with organizational performance, offering insights for researchers, HR practitioners, and bank regulators.